1998
DOI: 10.1002/(sici)1098-2264(199804)21:4<308::aid-gcc4>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Allelotyping demonstrates common and distinct patterns of chromosomal loss in human lung cancer types

Abstract: Allelic loss is a hallmark of tumor suppressor gene (TSG) inactivation. We have allelotyped 29 paired lymphoblastoid and lung cancer cell lines derived from 11 patients with small cell (SCLC) and 18 patients with non‐small cell lung carcinomas (NSCLC). Statistical analysis indicated that a threshold of 30% separated non‐random allelic loss from the random genetic deletions of malignancy. We have identified non‐random allelic loss at 42 of 54 (78%) specific chromosomal regions examined, with 22 regions (52%) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
97
0
4

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(112 citation statements)
references
References 42 publications
11
97
0
4
Order By: Relevance
“…Linkage analyses using microsatellite markers revealed deletions of 1p36 in nearly 50% of primary human lung cancers (Nomoto et al, 2000). Similar results were also reported in human lung cancer cell lines, including both NSCLC and small cell lung cancer (Virmani et al, 1998;Girard et al, 2000;Fujii et al, 2002). The evidence indicating the presence of a tumor-suppressor gene in 1p36 also comes from studies of mouse lung cancer.…”
Section: Discussionsupporting
confidence: 62%
“…Linkage analyses using microsatellite markers revealed deletions of 1p36 in nearly 50% of primary human lung cancers (Nomoto et al, 2000). Similar results were also reported in human lung cancer cell lines, including both NSCLC and small cell lung cancer (Virmani et al, 1998;Girard et al, 2000;Fujii et al, 2002). The evidence indicating the presence of a tumor-suppressor gene in 1p36 also comes from studies of mouse lung cancer.…”
Section: Discussionsupporting
confidence: 62%
“…43,44 These studies found that some LOH was common in both small cell carcinoma and non-small-cell carcinoma subtypes, whereas loss was subtype-specific in others. It has been suggested that the genetic alterations undergone by small cell carcinoma and non-smallcell carcinoma are different.…”
Section: Discussionmentioning
confidence: 99%
“…A range of atypical PJS tumours was also identified, including prostate and melanoma. Surprisingly, the highest mutation rate, hovering around 25% in multiple studies, was in lung adenocarcinomas, an established but uncommon PJSassociated tumour (Virmani et al, 1998;Sanchez-Cespedes et al, 2001) (Table 1).…”
Section: Lkb1 and Pjsmentioning
confidence: 99%